Knowledge, Attitudes and Opinions Towards Patient's Safety among Clinical Medical Students and General practitioners of Faculty of Medicine and Health Sciences at University and Hospital of Science and Technology, Yemen, Sana'a, 2025 - Ali, Ansam Naji; Ali, Eman Abdulwahab; Saeed, Hiba Tawfik; Faraj, Saleha Mohammed; Mohammed, Shaimaa Omar; Hussain, Haya Malek (My University, 2025)
Background: Patient safety became a global health issue to ensure high quality health care services and with minimal medical errors. Medical school education plays an important role in promoting patient safety culture during initial training. Objective: To assess the level of knowledge, attitudes and opinions about patient's safety and identify any significant differences among clinical medical students and general practitioners of faculty of Medicine and Health Sciences at University and Hospital of Science and Technology.